The models of territorial organization and management of the protected areas of the São Paulo coast with a focus on the Ilha do Cardoso State Park - de Lima Silva, Jéssica; de Oliveira, Regina Célia (Revista Geográfica de América Central., 2018)
This article analyzes the models of territorial and institutional organization of the Protected Areas of the South Coast of the State of São Paulo, focusing on the Ilha do Cardoso State Park - PEIC. Considerations are given regarding the importance of the organization of the Mosaics of Protected Areas of the South Coast and the role of the PEIC in the Conservation of biodiversity. Aspects of the unfolding of the institutionalization of the Park and its reflections are presented today. Coastal Protected Areas suffer from a series of land use pressures and socio-environmental issues. Significant changes have occurred in the Park in recent years, among which are the frequent needs that have arisen in the effort to reconcile the strategies of Management and Participatory Management with the demands of the traditional populations and their activities. Thus, management strategies are necessary in order for the objectives and functionalities of this Conservation Unit to be effective.